Reusable Aminated Lignin–Based Hydrogel Biocomposite for Effective Dye Adsorption in Wastewater - Roa-Ruiz, K; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2025)
This study reports enhanced organic dye adsorption capacity from aqueous solutions of a synthesized novel biocomposite hydrogel based on aminated lignin (AL) and poly(3-acryloamidopropyl)-trimethylammonium chloride P(ClAPTA). The biocomposites were characterized via Fourier-transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, and elemental analysis, confirming successful functionalization and polymerization. A factorial design was used to screen the operational parameters, showing that the P(ClAPTA-AL) composition was the most significant factor affecting dye adsorption compared to the amination ratio. Optimization of the adsorption process was achieved using alizarin red S (ARS) as a model dye through a Box–Behnken design, revealing optimal conditions: pH 12.0, 20 °C, 120 min contact time, and a composite-to-ARS mass ratio of 10, resulting in a high adsorption capacity of 102.1 mg g−1 and a maximum adsorption of 3889 mg g−1. Kinetic studies showed an adsorption process followed a pseudo-second-order model, confirming chemisorption as the predominant mechanism, while thermodynamic analysis revealed a spontaneous and endothermic adsorption process. Furthermore, promissory results demonstrated high reusability, with adsorption efficiency remaining at ∼99 % until the fourth cycle and maintaining 81.1 % after seven cycles. © 2025 Elsevier B.V.